Highly accelerated projection imaging with coil sensitivity encoding for rapid MRI. Issue 2 (1st February 2013) - Ersoz, Ali; Arpinar, Volkan Emre; Muftuler, L. Tugan
Abstract : Purpose: : Rapid magnetic resonance imaging (MRI) acquisition is typically achieved by acquiring all or most lines of k‐space after one radio frequency (RF) excitation. Parallel imaging techniques can further accelerate data acquisition by acquiring fewer phase‐encoded lines and utilizing the spatial sensitivity information of the RF coil arrays. The goal of this study was to develop a new MRI data acquisition and reconstruction technique that is capable of reconstructing a two‐dimensional (2D) image using highly undersampled k‐space data without any special hardware. Such a technique would be very efficient, as it would significantly reduce the time wasted during multiple RF excitations or phase encoding and gradient switching periods. Methods: : The essence of this new technique is to densely sample a small number of projections, which should be acquired at an angle other than 0° or multiples of 45°. This results in multiple rays passing through a voxel and provides new and independent measurements for each voxel. Then the images are reconstructed using the unique information coming from these projections combined with RF coil sensitivity profiles. The feasibility of this new technique was investigated with realistic simulations and experimental studies using a phantom and compared with conventional nonuniform fast Fourier transform technique. Eigenvalue analysis and error calculations were conducted to find optimal projection angles and minimum requirements for dense sampling. Results: : Reconstruction of 64 × 64 images was done using a single projection from simulated data under different noise levels. Simulated reconstruction was also tested with two projections to assess the improvement. Experimental phantom images were reconstructed at higher resolution using 4, 8, and 16 projections. Cross‐sectional profiles illustrate that the new technique resolved compartment boundaries clearly. Conclusions: : Simulations demonstrated that only a single k‐space line might be sufficient to reconstruct a 2D image using this new technique. Experimental results showed that this is a promising new technique for fast imaging. Using the information from the simulations and fast imaging parameters published in the literature, it could be predicted that a two‐dimensional image could be acquired in about 10 ms. One of the major advantages of this new technique is that it does not require any additional hardware and can be implemented on a conventional scanner with an eight‐channel coil.